Urban Archaeology in a Multi-Layered City: Conservation Challenges and Policy Insights from Istanbul's Historical Peninsula - Karacay, Nese; Ciftci, Aynur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Urban archaeology is one of the most fragile and non-renewable components of the historic urban landscape. In multi-layered cities such as Istanbul, where successive strata coexist within a dense and dynamic fabric, archaeological heritage is still largely addressed through rescue archaeology - a reactive intervention triggered only when construction exposes remains. This has often led to the isolation, inaccessibility, or reburial of significant sites, with little integration into the living city. This study focuses on eight cases in Istanbul's Historical Peninsula - a UNESCO World Heritage Site since 1985-to assess post-discovery conservation and presentation practices, identifying systemic barriers to effective integration. Based on site observations, archival and regulatory documents, and typological categorisation, it analyses legal, administrative, architectural, and educational dimensions, revealing weaknesses including fragmented legislation, institutional incoherence, inadequate spatial integration, and limited public presentation. Framing these findings within international conventions, including Valletta and Faro, the paper proposes policy insights for shifting from reactive rescue practices towards preventive and interpretive conservation. A multi-level, policy-oriented framework is proposed to integrate urban archaeological heritage into urban planning, ensuring both its material preservation and its ongoing role as a living component of Istanbul's cultural identity.
Keywords: Urban archaeology; multi-layered city; Istanbul Historical Peninsula; archaeological heritage management; conservation; CULTURAL-HERITAGE; PRESERVATION; MUSEALISATION; MUSEUM; SITES; Arts & Humanities - Other Topics